Pathogenic Organisms in Varanidae and Their Potential as Zoonotic Diseases - Syaiful Rizal; R A Rahmawati (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2021)
Monitor lizards have various body sizes, belong to the Varanidae and it is reported that there were various kinds of pathogenic organisms in their bodies. This review aims to describe various information on pathogenic organisms and their potential as zoonotic diseases and can be used as a reference in the prevention of zoonotic diseases originating from Varanidae. The results of this review discuss two types of viruses, three types of bacteria, five types of protozoa, two types of arthropods, and seven types of endoparasites that are pathogenic in Varanidae. Based on this information it is known that potentially zoonotic pathogens include bacteria group is Salmonella spp. and Anaplasma phagocytophilum; groups of protozoa was Giardia spp. and Cryptosporidium sp.; Arthropod group namely Amblyomma sp. which carries the bacteria Rickettsia sp., Borrelia spp. and Anaplasma spp. and the endoparasite group consisting of Ascaris sp., Strongyloides sp., Pentastomida, and Angiostrongylus cantonensis, while for the virus group, there were no pathogenic organisms with zoonotic potential. The extensive use of Varanidae by humans as exotic pets, as well as for consumption and medicine has great potential in the transmission of zoonotic diseases. Those are possible because the varanids non-aseptically environment. The proper handling and maintenance of monitor lizards are necessary to prevent the spread of zoonotic diseases. Unhygienic and less aseptic way of handling food products of animal origin can lead to the potential for transmission of pathogenic organisms (foodborne disease). Efforts to prevent the transmission of foodborne diseases can apply Good Hygienic Practices (GHP) with the process of cooking reptile meat for consumption. Besides, disease transmission can be prevented by implementing the One Health concept.